Women Who Have Experienced Pregnancy Loss: Implications for Counseling. (October 2021) - Randolph, Amber L.; Swanson, Renae; Smith, Allyson; Ojeda, Katherine
The purpose of this research was to explore women's experiences of pregnancy loss. The following five themes were identified: (a) grief and new emotions, (b) social aspects, (c) meaning making, (d) subsequent pregnancies, and (e) what was and would have been helpful. The results indicate that counselors can be instrumental in the healing of women who have experienced pregnancy loss. Specifically, counselors can help clients communicate effectively with their families, partners, and social networks post-loss.